Pelatihan Pemanfaatan Kecerdasan Buatan untuk Meningkatkan Kreativitas dan Literasi Digital Siswa MA Mu'allimat NWDI Kelayu - Ida Wahidah; Putra, Hadian Mandala; Darmawan, Muhammad Iman; Nuzuluddin, M (Universitas Hamzanwadi, 2025)
The integration of technology in education, particularly Artificial Intelligence (AI) and Cloud Computing, is crucial in facing the Society 5.0 era. This study aims to analyze the effectiveness of AI and cloud technology training and its impact on students' understanding and perception. The research method utilized a quantitative descriptive approach through pre-implementation and post-implementation questionnaires distributed to 35 respondents, predominantly aged 16-18 years. Initial survey results indicated that while 77.1% of students had heard of AI, there was a gap in understanding, with 34.3% of respondents feeling they had poor or no understanding at all. Furthermore, cloud technology usage remained low, with 48.6% of students stating they had never used it. Following the training implementation, evaluation showed significant improvement, where 77.1% of respondents felt they understood the utilization of AI and cloud technology better. Participant satisfaction was high, with 85.8% rating the material as useful to very useful. The primary challenge identified was a lack of foundational understanding (65.7%). Overall, the program successfully enhanced participants' digital literacy, with 77.1% of students hoping that these technologies will improve the quality of learning in the future.